Adaptive Criminal Liability for Persons with Disabilities: A Review of Criminal Reduction and Elimination Policies in the National Criminal Code: PertanggungJawaban Pidana yang Adaptif dalam Reformasi Hukum Nasional: Mengakomodasi Gangguan Mental dalam Hukum Pidana - Fazacholil, M. Ghufron; Saefudin, Yusuf (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2025)
The reformulation of criminal liability in the New Criminal Code through Articles 38 and 39 demonstrates the commitment of the Indonesian criminal law system to accommodate the principle of inclusive justice for persons with mental and/or intellectual disabilities. This article discusses the elimination and reduction of punishment for perpetrators with disabilities from a normative perspective, as well as the challenges of its implementation at the practical level. In the old Criminal Code, Article 44 only provides general criminal exemptions without procedural clarity and alternative measures. The 2023 Criminal Code, which will enter into force in 2026, changes this approach by distinguishing between offenders who are still able to understand the consequences of their actions (subject to punishment with reduction or alternative measures) and offenders who are in an acute state and unable to understand (subject to measures without punishment). This article uses a normative juridical approach and is supported by limited empirical juridical analysis to examine the effectiveness and challenges of this new provision. The results of the study show that Articles 38 and 39 have shifted the paradigm of punishment from retributive to humanistic, but their implementation still faces obstacles, especially regarding technical guidelines for assessing mental capacity, expert involvement, and potential treatment disparities. Therefore, a lex specialis is needed to support the general provisions so that they can be operationalized effectively, fairly, and non-discriminatively against persons with disabilities in the criminal law process.